The Effect of the School Leadership Style and Completeness of Infrastructure Facilities on Teacher Performance - Santi, Santi; Fitria, Happy; Nurlina, Nurlina (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine the influence of the principal's leadership style and completeness of infrastructure on teacher performance. The location of this research was carried out in public junior high schools in Mesuji District. This type of research is quantitative research with research design using research design after the fact. The sample in this study was a total of all teachers in public junior high schools in Mesuji District, consisting of 89 respondents. Data collection techniques using a questionnaire. Data analysis techniques using descriptive quantitative analysis techniques, and multiple regression. The results of this study state that 1) there is a significant influence between the Principal's Leadership Style on the Performance of State Middle School Teachers in Mesuji District; 2) there is a significant effect of Completeness of Infrastructure on the Performance of State Middle School Teachers in Mesuji District; 3) there is a significant influence of the Principal's Leadership Style and Completeness of Infrastructure together on the Performance of State Middle School teachers in the Mesuji District.